2018
DOI: 10.3389/fncom.2018.00096
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for Modeling Neural Responses to Joint Perturbations Using the NARMAX Method and a Hierarchical Neural Network

Abstract: The human nervous system is an ensemble of connected neuronal networks. Modeling and system identification of the human nervous system helps us understand how the brain processes sensory input and controls responses at the systems level. This study aims to propose an advanced approach based on a hierarchical neural network and non-linear system identification method to model neural activity in the nervous system in response to an external somatosensory input. The proposed approach incorporates basic concepts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Neuronal processing of synaptic inputs can lead to the modulation of inter-spike intervals which produces cross-frequency coupling, i.e., synchronization across different frequencies between input and output (Koch and Segev, 2000;Markram, 2003;Yang et al, 2018). Our previous work on multisynaptic ascending sensory pathways (Yang et al, 2016b;Tian et al, 2018), as well as a recent opinion article (Yang et al, 2018), argued that multi-synaptic interaction in a neural pathway can lead to a substantial expression of cross-frequency coupling. However, insights into possible mechanisms underlying neural coupling in the multi-synaptic descending motor pathways are currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Neuronal processing of synaptic inputs can lead to the modulation of inter-spike intervals which produces cross-frequency coupling, i.e., synchronization across different frequencies between input and output (Koch and Segev, 2000;Markram, 2003;Yang et al, 2018). Our previous work on multisynaptic ascending sensory pathways (Yang et al, 2016b;Tian et al, 2018), as well as a recent opinion article (Yang et al, 2018), argued that multi-synaptic interaction in a neural pathway can lead to a substantial expression of cross-frequency coupling. However, insights into possible mechanisms underlying neural coupling in the multi-synaptic descending motor pathways are currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental procedure was approved by the Human Research Ethics Committee of the Delft University of Technology. The multi-sine signal contained nine sinusoids with frequencies of 5,7,9,11,13,16,17,23,29 Hz and randomly chosen phases. Previous studies have indicated the importance of the second-order nonlinearity in the human proprioceptive system [3,23,24].…”
Section: E Application To the Human Proprioceptive Systemmentioning
confidence: 99%
“…Previous studies have indicated the importance of the second-order nonlinearity in the human proprioceptive system [3,23,24]. The designed multi-sine signal allows generation of nonlinear cortical response in different EEG frequency bands, including alpha (10-15 Hz), beta (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and gamma bands (> 30 Hz)., which allows to check whether the amplitude transfer in the human proprioceptive system is mediated by the dynamics of any specific brain rhythms. The period of the multisine signal was 1 s and the peak-to-peak value was 0.06 radians.…”
Section: E Application To the Human Proprioceptive Systemmentioning
confidence: 99%
See 2 more Smart Citations